2001
DOI: 10.7326/0003-4819-135-5-200109040-00007
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Activity among Community-Living Older Persons: Incidence, Precipitants, and Health Care Utilization

Abstract: Restricted activity is common among community-living older persons, regardless of risk for disability, and it is usually attributable to several concurrent health-related problems. Although restricted activity is associated with a substantial increase in health care utilization, older persons with restricted activity often do not seek medical attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
377
2
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 288 publications
(398 citation statements)
references
References 27 publications
9
377
2
4
Order By: Relevance
“…The co-occurrence of different causes of disability in more than two-thirds of the cases supported our decision of using general syndromes in the case definition, which allowed for an easy definition of the cases, even if some of them could be related to other nonmusculoskeletal problems. The specific diagnoses by GPs were mostly axial and peripheral osteoarthritis, followed by soft tissue problems and inflammatory diseases, as expected (2,8,16,24,25). The presence of a high Charlson index, a high level of pain, and associated MSD comorbidities reflects the spectrum of the more prevalent diseases at this age (26) and gives a clear idea of the complex management needed to improve the situation.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The co-occurrence of different causes of disability in more than two-thirds of the cases supported our decision of using general syndromes in the case definition, which allowed for an easy definition of the cases, even if some of them could be related to other nonmusculoskeletal problems. The specific diagnoses by GPs were mostly axial and peripheral osteoarthritis, followed by soft tissue problems and inflammatory diseases, as expected (2,8,16,24,25). The presence of a high Charlson index, a high level of pain, and associated MSD comorbidities reflects the spectrum of the more prevalent diseases at this age (26) and gives a clear idea of the complex management needed to improve the situation.…”
Section: Discussionsupporting
confidence: 62%
“…The Rosser system (21) classifies function and mobility in 8 different levels, and we determined the fourth level as the cut point, mostly because it reflects well when physical disability, in addition to an individual health problem, starts to be a societal challenge. When we compared other incidence studies, our estimations were lower (16,22). In the study by Gill et al (16,22), restricted activity was identified by monthly calls, but included all causes of disability and was directed to a previously selected, high-risk population.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Two cross-sectional studies show that older persons who report fatigue have significantly less good physical performance (61,62), slower walking speed, and more mobility-and IADL-disability (62). A few longitudinal studies show that participants with fatigue have more restricted activity at 1½ year follow-up (63), poorer physical function, ADL and slower gait speed at 3-year follow-up (64), increased healthcare utilization and mortality (15), and higher risk of mortality during 10-year follow-up (65).…”
Section: © 2 0 1 0 E D I T R I C E K U R T I S F O R P E R S O N a mentioning
confidence: 99%